Determinan Keputusan Pengambilan Pembiayaan UMKM di Lembaga Keuangan Syariah dengan Variabel Kontrol Faktor Demografi - Febrianti, Fika; Purwidianti, Wida; Handayani, Erna; Yusnar, Alfato (Universitas Islam Negeri Alauddin Makassar, 2023)
This research aims to determined the effect of financial literacy, procedures, and profit sharing on financing decisions with demographic factors as a control variable in Islamic financial institutions. Sampling technique using convenience sampling with a number sample of 105 MSME actors in Banyumas Regency. Data testing in this research used software tools, namely the SmartPLS 3.0 application. The results of this study showed that: (1) Financial Literacy has a significant effect on financing decisions. (2) the procedure has no significant effect on financing decisions. (3) revenue sharing has a significant effect on financing decisions. (4) the level of education as a control variable does not control the effect of financial literacy, procedures, and profit sharing on financing decisions. (5) income as a control variable can control the influence of financial literacy, procedures, and profit sharing on financing decisions. Keywords: Financial literacy, Procedures, Profit Sharing, Demographic Factors, Financing decision making.